Regulation of Adaptive Immune Cells by Sirtuins - Warren, Jonathan L.; MacIver, Nancie J. (Frontiers in Endocrinology, 2019)
It is now well established that the pathways that control lymphocyte metabolism and function are intimately linked, and changes in lymphocyte metabolism can influence and direct cellular function. Interestingly, a number of recent advances indicate that lymphocyte identity and metabolism is partially controlled via epigenetic regulation. Epigenetic mechanisms, such as changes in DNA methylation or histone acetylation, have been found to alter immune function and play a role in numerous chronic disease states. There are several enzymes that can mediate epigenetic changes; of particular interest are sirtuins, protein deacetylases that mediate adaptive responses to a variety of stresses (including calorie restriction and metabolic stress) and are now understood to play a significant role in immunity. This review will focus on recent advances in the understanding of how sirtuins affect the adaptive immune system. These pathways are of significant interest as therapeutic targets for the treatment of autoimmunity, cancer, and transplant tolerance.